THE ROLE OF TSO (THIRD SECTOR ORGANIZATION) TOWARDS THE EMPOWERMENT OF WOMEN IN BALI (CASE STUDY: BALI SRUTI) - Arnold Arswenda Kusuma (International Journal of Economics Management and Social Science, 2018)
The issue of gender inequality in Indonesia is the result of a patriarchal culture that has existed for a long time. The gender division of men and women in the field of social and economic development is clearly visible, as women do not fully gain access to some resource sectors, such as education and employment. Bali as one of the provinces in Indonesia that still adheres to patriarchal culture. But the culture is in fact contrary to the Hindu belief that they believe to be the majority religion, where women have a very respectable position because it is considered as the incarnation of one of the revered Goddesses. This then underlies the movement of one of the TSO (Third Sector Organization) in Bali, Bali Sruti, which then consistently campaigns for women empowerment. In this paper the authors found that the role of Bali Sruti in their efforts to empower women in Bali includes several things, such as the socialization of women's participation in politics, the socialization of pluralism, and interactive discussions through interactive radio in relation to gender equality issues aimed at increasing the participation of Balinese women in sustainable social and economic development.